[BP.07.02] CARDIAC BLOOD SUPPLY-WORKLOAD BALANCE IN PEDIATRIC PATIENTS AFTER AORTIC ARCH REPAIR. (September 2017) - Murakami, T.; Shiraishi, M.; Takeda, A.
Abstract : Objective: One of the most important problems in patients with aortic coarctation after aortic arch repair is a future cardiovascular disease (hypertension, myocardial infarction, cerebrovascular disorders, cardiac failure and sudden death). We previously reported that a new pressure wave reflection occurred from the surgically repaired site. It could increase the cardiac workload of them. Therefore, we examined the cardiac blood supply-workload balance in patients after aortic arch repair. Design and method: Seventeen patients after aortic arch repair without pressure gradient after repaired site were enrolled. A pressure sensor mounted catheter recorded pressure waveform in ascending aorta. From the pressure waveform, we analyzed subendocardial viability ratio. The data were compared with those of age-matched patients with a normal aortic arch, because the index increases with growth in childhood. Results: The patient's age was 6.8 ± 2.8 years and they underwent the aortic arch repair at 0.08 ± 0.08 years. The systolic blood pressure at ascending aorta was 100.3 ± 9.9 mmHg and cardiac index was 4.1 ± 0.7 l/min m 2 . There was no difference in the subendocardial viability ratio between the arch repair group and control group (1.0 ± 0.2 vs. 0.9 ± 0.1). However, tension time index (27.4 ± 5.6 vs. 23.2 ± 3.6, p = 0.0028), which means the workload of the heart, and diastolic pressure time index (28.4 ± 11.1 vs. 21.6 ± 5.0, p = 0.0154), which means the blood supply to the heart, significantly increased in patients after aortic arch repair comparing those in control subjects. Conclusions: In pediatric patients after aortic arch repair, the cardiac blood supply-workload balance is kept. However the workload increases. The compensation could brake down in days ahead and it may one of the causes the future cardiovascular diseases.